Determinants of Micro, Small and Medium Enterprises (SMEs) Performance - Bakari, Said Moh Agus B; Abdul, Irawati; Dai, Sri Indriyani S. (Universitas Gorontalo, 2024)
This study aims to analyze the influence of capital, human resources and technology on the performance of micro, small and medium enterprises (SMEs) in Gorontalo City.Â The analysis method uses multiple linear regression with a crossection approach. The data used in this study was primary data sourced from 30 respondents. The results of this study show that: 1) capital has a negative insignificant effect on the performance of SMEs; 2) human resources have a positive insignificant effect on MSME performance and 3) technology has a significant positive effect on SMEs performance. This study provides practical implications for the government as a policy maker in an effort to improve the performance and empowerment of SMEs, especially in Gorontalo City.Â Â